The Midwifery Workforce: ACNM 2012 and AMCB 2013 Core Data. (December 2015) - Fullerton, Judith; Sipe, Theresa Ann; Hastings‐Tolsma, Marie; McFarlin, Barbara L.; Schuiling, Kerri; Bright, Carrie D.; Havens, Lori B.; Krulewitch, Cara J.
Abstract : Introduction: Core data are crucial for detailing an accurate profile of the midwifery workforce in the United States. The American College of Nurse‐Midwives (ACNM) and the American Midwifery Certification Board, Inc. (AMCB), at the request and with support from the US Health Resources and Services Administration (HRSA), are engaged in a collaborative effort to develop a data collection strategy (the Midwifery MasterFile) that will reflect demographic and practice characteristics of certified nurse‐midwives (CNMs) and certified midwives (CMs) in the United States. Methods: Two independent datasets, one collected by ACNM in 2012 and one by AMCB in 2013, were examined to determine key workforce information. ACNM data were collected from the online Core Data Survey sent to ACNM members. AMCB data were extracted from information submitted online by applicants seeking initial certification in 2013 and applicants seeking to recertify following 5 years of initial certification. Results: The ACNM 2012 survey was partially or fully completed by 36% (n = 2185) of ACNM members (N = 6072). AMCB respondents included 100% of new certificants (N = 539) and those applying for recertification in 2013 (n = 1323) of the total 11, 682 certificants in the AMCB database. These two datasets demonstrate that midwives remain largely white, female, and older in age, with most engaged in clinical midwifery while employed primarily by hospitals and medical centers. Differences were reported between the ACNM membership and AMCB certification datasets in the numbers of midwives holding other certifications, working full‐time, attending births, and providing newborn care. Discussion: The new collaboration among HRSA, ACNM, and AMCB, represented as the Midwifery MasterFile, provides the opportunity to clearly profile CNMs/CMs, distinct from advanced practice registered nurses, in government reports about the health care workforce. This information is central to identifying and marketing the role and contribution of CNMs/CMs in the provision of primary and reproductive health care services.